(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
Polycrystalline NiFe2O4 was prepared by solid state reaction from nano size powder of NiO and Fe2O3 which were synthesized by wet chemical method. The inverse spinel single phase of the sample has been confirmed by the X-ray diffraction patterns. SEM micrographs of the samples revealed that the grain size increases and the porosity decreases with the increase in sintering temperature and has great influence on the magnetic properties of NiFe2O4 . Enhancement of real part of initial permeability (μ′) as a function of frequency has been observed with the increase in sintering temperature. Temperature dependence real part of initial permeability has been observed at various sintering temperature and gives the manifestation of Hopkinson effect. Variation of Curie temperature (Tc) has been found with the variation of sintering temperature. Key words: Sintering temperature; Microstructure; Magnetic properties DOI: 10.3329/jbas.v34i2.6865 Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 189-195, 2010